Paving the way towards circular consumption: exploring consumer acceptance of refurbished mobile phones in the Dutch market. (1st February 2016) - van Weelden, Eline; Mugge, Ruth; Bakker, Conny
Abstract: In the transition towards a circular economy, refurbishment can be applied to regain value from used products, and to reduce waste. Refurbishment is a process in which a professional company collects and restores used products in order to resell these products to new consumers. Building on insights from the remanufacturing literature, this research is the first to provide a comprehensive understanding of the factors that influence consumer acceptance of refurbished products, and in specific refurbished mobile phones. We adopted a qualitative approach using in-depth interviews with consumers (n = 20) of new and refurbished phones to gain rich insights into consumers' considerations that play a role in the choice of a refurbished product over a new product. This paper maps out the main factors that influence consumer acceptance of refurbished mobile phones. Our findings uncover that the majority of consumers do not take a refurbished product into consideration as a consequence of a lack of awareness and a misunderstanding of what refurbishment actually entails. In addition, refurbished products are often rejected as a consequence of a negative trade-off between perceived risks and benefits. Personal, contextual and product-related factors have been identified that influence consumers' assessment of a refurbished product's risks and benefits. Finally, the findings have been translated into practical guidelines for designers and marketers to positively steer consumer perception of refurbished products. Highlights: This paper uncovers the factors that influence consumer acceptance of refurbished products. Refurbished products are rejected at different moments in the consumer decision-making process. A lack of familiarity with refurbished products is a major cause of current low consumer acceptance. A distinctive and positive image of refurbished products is critical for consumer acceptance.